Study Theological Approach on Abortion Actions based on Psalm 139:13 and the Responsibility of Today’s Church Leaders - Darius, Trisnawadi (KAMASEAN: Jurnal Teologi Kristen, 2024)
The church is a community united by the Lord Jesus Christ, empowered to be witnesses, agents, and examples. However, reality shows that the church often tends to be closed off and does not consistently practice God's love and justice, whether towards its congregation, among church organizations, or towards the surrounding environment, particularly concerning the issue of abortion among teenagers and young people. This study aims to analyse abortion in light of Psalm 139:13 and outline contemporary church leaders' responsibilities. The methodology employed is qualitative, using a literature-based approach (library research) grounded in hermeneutical study. Hermeneutics universally refers to the theoretical and methodological process of understanding the meanings of signs and symbols used in verbal or non-verbal communication. The approach used is the grammatical-historical study approach. The results of this research indicate that abortion of unwanted foetuses is inconsistent with biblical teachings; therefore, contemporary church leaders have a responsibility to nurture the morality of youth to help them avoid engaging in premarital sex, which could lead to abortion.